HUBUNGAN ANTARA TINGKAT KECEMASAN DENGAN INDEKS MASSA TUBUH PADA MAHASISWA UPN "VETERAN" JAKARTA - Muhammad Adhipramana (2023)
The number of teenagers in Indonesia is 64.92 million in 2021. Adolescence is a transitional stage in a person's life between the stages of childhood and adulthood. At this time of transition usually involves anxiety. Anxiety in adolescents can significantly interfere with daily activities. Anxiety also be a factor affecting body mass index in adolescents. Research Purposes : To determine the correlation between anxiety levels and body mass index in final students at the Faculty of Social and Political Sciences in UPN Veterans Jakarta. Methods: This study used a correlational quantitative research design with a cross-sectional approach. The sample in this study was 133 students. In this study, univariate tests and bivariate tests were used using SPSS 25. Results: The results obtained for the most anxiety scores were in the moderate anxiety category with a percentage of 50.4% and the highest body mass index values were in the normal category with a percentage of 31.6%. After the correlation test, it was found that there was no significant relationship between anxiety and body mass index, with p=0.703 (p<0.05). The conclusion of this study is that there is no significant relationship between anxiety and body mass index.